1999
DOI: 10.1007/bf02236937
|View full text |Cite
|
Sign up to set email alerts
|

Short chain fatty acids are effective in short-term treatment of chronic radiation proctitis

Abstract: Short chain fatty acid enemas can accelerate the process of healing in chronic radiation proctitis, but treatment has to be continuous if a complete and sustained clinical, endoscopic, and histologic response is to be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 25 publications
0
57
0
5
Order By: Relevance
“…SCFAs cause greater blood flow to the intestinal wall through diminishing the resistance of the arterioles of the colon and rectum. They promote adhesion between the colonocytes, increase sodium and water absorption, stimulate normal growth of the colon epithelial cells, influence motility and favor healing of intestinal wall lesions 15,16,17 . SCFAs play a protective role in relation to neoplasia development because their antiproliferative action interferes in the cell differentiation process, thereby favoring apoptosis 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFAs cause greater blood flow to the intestinal wall through diminishing the resistance of the arterioles of the colon and rectum. They promote adhesion between the colonocytes, increase sodium and water absorption, stimulate normal growth of the colon epithelial cells, influence motility and favor healing of intestinal wall lesions 15,16,17 . SCFAs play a protective role in relation to neoplasia development because their antiproliferative action interferes in the cell differentiation process, thereby favoring apoptosis 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…They promote adhesion between the colonocytes, increase sodium and water absorption, stimulate normal growth of the colon epithelial cells, influence motility and favor healing of intestinal wall lesions 15,16,17 . SCFAs play a protective role in relation to neoplasia development because their antiproliferative action interferes in the cell differentiation process, thereby favoring apoptosis 17,18 . In segments without intestinal transit, glutamine (a secondary energy substrate for the epithelium that is mainly supplied by the blood) comes to have a primary role and may be used in preference to glucose as an energy source 19 .…”
Section: Discussionmentioning
confidence: 99%
“…53 Several studies of SCFA enemas to promote healing of postradiation mucosal lesions have yielded conflicting results. Initial studies indicated a decrease in rectal bleeding and endoscopic improvements with SCFA use, [54][55][56] but those findings were not reproduced in a subsequent prospective, randomized, double-blind study.…”
Section: Short-chain Fatty Acid Enemasmentioning
confidence: 98%
“…Talley et al (1997) was a cross-over study and used a cumulative score encompassing the number of episodes of rectal bleeding per week. Pinto et al (1999) recorded the number of days on which rectal bleeding occurred. Although both sets of cases were scored endoscopically, this is not on the same scale so that the numbers are not comparable.…”
Section: Studies Using Scfa Enemasmentioning
confidence: 99%